2006
DOI: 10.1080/03610730600699100
|View full text |Cite
|
Sign up to set email alerts
|

Remembering the Past and Foreseeing the Future while Dealing with the Present: A Comparison of Young Adult and Elderly Cohorts on a Multitask Simulation of Occupational Activities

Abstract: Thirty-five young adult and 38 elderly cybernauts, matched for education, sex, alcohol consumption, and time/day of computer use were compared on a computerized simulation of professional activities of daily living (ADLs). The program quantified performance in terms of speed and accuracy on four major constructs: (1) planning (a 30-item office party script); (2) prospective memory (injections, sleep, phone); (3) working memory (PASAT, D2, and CES analogs); and (4) retrospective memory. Participants had to orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…At the very least, the effect of age would have to be partialed out of the main test of the central hypothesis. Second, Guimond et al (2006) and Aylward, Brager, and Harper (2002) have found that normal ageing is characterised by a significant shift towards omissiveness over commissiveness on memory tests and other cognitive tests. Thus again, ageing could bias the results of the current study by contributing noise, or even a nefarious bias to the test of our main hypothesis (the interaction between type of memory disturbance and lesion side).…”
Section: Post Unilateral Lesion Memory Disturbancementioning
confidence: 98%
See 1 more Smart Citation
“…At the very least, the effect of age would have to be partialed out of the main test of the central hypothesis. Second, Guimond et al (2006) and Aylward, Brager, and Harper (2002) have found that normal ageing is characterised by a significant shift towards omissiveness over commissiveness on memory tests and other cognitive tests. Thus again, ageing could bias the results of the current study by contributing noise, or even a nefarious bias to the test of our main hypothesis (the interaction between type of memory disturbance and lesion side).…”
Section: Post Unilateral Lesion Memory Disturbancementioning
confidence: 98%
“…There are two reasons why the difference between middle-age and elderliness might be relevant to the types of memory dysfunction investigated here. First, memory impairment is one of the most radical cognitive manifestations of ageing in the general population (Guimond, Braun, Rouleau, & Godbout, 2006). It can therefore be imagined that amnesic symptoms, more than commissive symptoms, could be related to advancing age, adding variance to the effect of unilateral lesions and complicating interpretation of the effect of lesions in the present database.…”
Section: Post Unilateral Lesion Memory Disturbancementioning
confidence: 99%
“…However, though the effect was in the predicted direction in the left-lesioned group, in the present investigation it was far from significance. For details of the Lesionside × Response-bias interaction, subtask by subtask on RLASv10, see Guimond's (2011) PhD thesis [53].…”
Section: Resultsmentioning
confidence: 99%
“…The research tool designed for the present experiment was a multitask occupational computer simula-tion called RLAS, which has been shown to be highly reflective of cognitive decline related to normal aging [53] and to brain lesions [52]. It generates normally distributed performances devoid of ceiling effects [54].…”
Section: The Real-life Activities Simulation (Rlas)mentioning
confidence: 99%
“…occasionally forgetting to keep an appointment) become more prevalent (Bä ckman et al 2004, Guimond et al 2006. Kliegel and Jä ger (2006) examined prospective and working memory among four age-groupings (n = 127), separating older adults by 10-year groupings from age 60 to 91 years; the data derived were then compared to those from a group of younger people ranging from age 22 to 31 years.…”
Section: Retrieval Induced Forgettingmentioning
confidence: 99%